Pengembangan Multimedia Interaktif Life Loop pada Materi Siklus Hidup Makhluk Hidup Kelas III di SDN Junganyar 2 Socah - Ajib Akhmad Fadhoni; Andika Adinanda Siswoyo (Mataram University, 2026)
The learning process of science (IPAS) in elementary schools still faces several challenges, particularly in teaching abstract concepts such as the life cycle of living things, which often result in low student engagement and learning outcomes. In addition, the limited use of interactive digital learning media has made it difficult for teachers to create meaningful and student-centered learning experiences. This study aims to: (1) develop a valid Life Loop interactive multimedia based on the results of the validation questionnaire; (2) develop an effective Life Loop interactive multimedia reviewed from the learning outcomes and the results of observations of teacher and student activities; and (3) develop an interesting Life Loop interactive multimedia based on teacher and student response questionnaires. This study uses the Research and Development (R&D) development method with the ADDIE research model with 32 students as research subjects. The results of the study show that the interactive multimedia developed is included in the very valid category, with validation results from media experts of 95%, material experts of 82%, and learning design experts of 87%. The effectiveness of interactive multimedia is proven through large group trials, where the results of observations of teacher activities obtained a percentage of 100% with an active category, while student activities reached 96.80% with an active category. In addition, the results of the evaluation test showed that 27 students who took the test had achieved individual learning completion. The level of interactive multimedia interest is also very high, as shown by the results of the teacher response questionnaire of 98.33% and the student response of 95.46%, both of which are included in the very interesting category. Based on the overall results, the Life Loop interactive multimedia is declared suitable for use in science (IPAS) learning for Grade III students at SDN Junganyar 2 Socah Bangkalan on the topic of the life cycle of living things.